THE INFLUENCE OF ORGANIZATIONAL CULTURE ON EMPLOYEE PERFORMANCE WITH THE WORK ENVIRONMENT AS A MODERATION VARIABLE (STUDY OF PUSKESMAS EMPLOYEES IN BREBES) - Setyowati Subroto; Ira Maya Hapsari; Yanti Puji Astutie (SEAN Institute, 2023)
This study aims to examine and determine the influence of organizational culture on employee performance; testing and knowing the effect of the work environment on employee performance and testing and knowing the influence of organizational culture on employee performance with the work envorinment as moderating variable. This study used quantitave methods, and the sample was taken using cluster sampling technique, with a total sample of 63 employess (doctors, nurses and midwives) at Pemaron, Jatibarang and Bumiayu Brebes Public Health Centers. The data collection method used a questionnaire consisting of statements about organizational culture, work environment and performance. While the data analysis technique uses a moderated regression analysis (MRA) model with the help of smartPLS. This results show that (1) organizational culture has no effect on employee performance because the P values > 0,005; (2) the work environment has no effect on employee performance with P values < 0,05; dan (3) organizational culture as no effect on employee performance with the work environment as a moderating variable, because the P values > 0,05. This study shows that organizational culture can frow and develop because there are human resources who have high morale who can improve performance, in addition to having a good work environment will be able to provide motivation to work and the achievement of performance can increase compliance with organizational culture even without intermediary work environment.